Dispute Over Non-Compliance of Online Lending Companies Based on Financial Services Authority Regulations (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2025)
The purpose of this study is to determine how to resolve disputes regarding PT Investree Radhika Jaya's non-compliance in violation of Financial Services Authority Regulation Number: 77 / POJK.01 / 2016 concerning Information Technology-Based Money Lending Services and Number 10 / POJK.05 / 2022 concerning Information Technology-Based Joint Funding Services and Legal Protection for Lenders (lenders) against PT Investree Radhika Jaya's Non-Compliance. The presence of Peer to Peer Lending / online loans as the latest innovation in making loans, the process is very easy and does not require collateral. But only based on the principle of good faith. Management of loan money provided by Lenders to Borrowers is carried out through an online system by the Organizer, so that Lenders do not know which customers the funds are given to. The increasingly sophisticated online loan procedures cause problems, due to the lack of transparency of the information system for funds that have been distributed from the organizer to the Borrower, because everything is controlled by the organizer. So that the benefits that should be given by the Organizer to the Lender are not given. This study uses a normative method by reviewing the regulations of the Financial Services Authority Number: 77 / POJK.01 / 2016 and Number 10 / POJK.05 / 2022. The results of this study. First, the settlement of disputes in dealing with non-compliance of the organizer (PT Investree Radhika Jaya) is that the OJK issues administrative sanctions in the form of revocation of business licenses. Second, legal protection for Lenders can be applied in two ways, namely the Implementation of preventive legal protection by issuing laws and regulations that limit an obligation and prevent a violation. The provisions issued by the OJK as preventive legal protection are POJK No. 77 / POJK.01 / 2016. While Repressive Protection is given when a violation has occurred, namely the OJK revokes the business license of PT Investree Radhika Jaya dissertation with the liquidation